New method for self-heating estimation using only DC measurements - Mori, C. A.B.; Agopian, P. G.D. [UNESP]; Martino, J. A. (Institute of Electrical and Electronics Engineers (IEEE), 2018)
This paper reports a new method for estimating the thermal resistance of a device using the inverse of the transistor efficiency as a function of the power applied to the transistor's channel. The advantages of this new method are the use of DC measurements only and errors smaller than 4% in the estimation of the channel temperature increase due to the SHE when compared to a pulsed method for the UTBB SOI studied in this work.
Keywords: Self-heating effect; Silicon-On-Insulator; UTBB